2014
DOI: 10.1002/adma.201404306
|View full text |Cite
|
Sign up to set email alerts
|

A New Application Area for Fullerenes: Voltage Stabilizers for Power Cable Insulation

Abstract: Fullerenes are shown to be efficient voltage-stabilizers for polyethylene, i.e., additives that increase the dielectric strength of the insulation material. Such compounds are highly sought-after because their use in power-cable insulation may considerably enhance the transmission efficiency of tomorrow's power grids. On a molal basis, fullerenes are the most efficient voltage stabilizers reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 25 publications
1
69
0
Order By: Relevance
“…Randomness and dispersion of DC breakdown cannot be prevented even under identical conditions. It is recognized that the two-parameter Weibull probability can fit the DC breakdown strength of solid materials effectively with the following expression [27]:…”
Section: Fig 1 Sem Section Images Of Xlpe/sic 32 DC Breakdownmentioning
confidence: 99%
“…Randomness and dispersion of DC breakdown cannot be prevented even under identical conditions. It is recognized that the two-parameter Weibull probability can fit the DC breakdown strength of solid materials effectively with the following expression [27]:…”
Section: Fig 1 Sem Section Images Of Xlpe/sic 32 DC Breakdownmentioning
confidence: 99%
“…Researchers have tried many ways to improve the electrical tree breakdown resistance of high voltage (HV) cables, including material blending modification, nanoparticle modification, and polycyclic compound modification [4][5][6]. Results showed that polycyclic compound had an excellent function of suppressing electrical treeing in polymeric insulating material [7,8]. The America Dow Chemical Company studied the effects of a series of siloxane polycyclic compounds containing pendant aromatic groups on the growth characteristics of electrical tree.…”
Section: Introductionmentioning
confidence: 99%
“…The higher value of "n" represents the longer service life of the cable. The global cable manufacturers have adopted the recommended values (France: n = 20, Sweden: n = 9) or acceptable limits of "n" (Japan: n = 10-19, Germany: 10-17, Netherlands: n = [19][20]. Similarly, Chinese cable industry recommends that the "n" within the range from 12 up to 16 [5].…”
Section: Introductionmentioning
confidence: 99%